Market Concentration, Bank Characteristics, Macroeconomic Conditions, and Indonesian Islamic Bank Financing - Misanam, Munrokhim; Widarjono, Agus (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2023)
As the latest player in the banking market in Indonesia, Islamic banks are not as experienced as their counterpart conventional banks. In addition, the types of Islamic bank financing (loans) are different from conventional bank loans. Our work investigates the determinants of Islamic bank financing in Indonesia. Our concern variables are market concentration, bank fundamentals, and macroeconomic conditions, including Covid-19. This study examines all Islamic banks in Indonesia from 2015 to 2020 using quarterly data. Our data set is 724 observations with unbalanced panel data. We employ the dynamic panel data using the two-step system GMM that is more robust than two-step difference GMM. Market  concentration encourages financing. Profitability, bank size, and financing loss provision also enhance financing. However, a high degree of risk aversion and inefficiency reduces financing. Furthermore, Islamic bank financing also depends on macroeconomic conditions. Economic upturns strengthen financing. Strong bank fundamentals, particularly bank size, are the key to success for Islamic bank financing. The results draw an important practical implication. Large Islamic bank is a necessary condition to compete with a conventional bank. Accordingly, the spin off policy of Islamic bank windows to full-fledged Islamic bank should be implemented immediately.